Role of medicinal plants and their chemical constituents in ameliorating the cause for non-alcoholic fatty liver disorder—A review - Singh Anuragh, Kaliappan Ilango (Journal of Applied Pharmaceutical Science, 2022)
Non-alcoholic fatty liver disease (NAFLD), a silent epidemic, is one of the global threats linked with various concerns that can lead to chronic liver diseases. It is the most common liver disorder in Asian and Western countries, a continuum of ailments ranging from simple steatosis to steatohepatitis, cirrhosis, and liver carcinoma. Youngsters are lured with sugary beverages and other kinds of junk foods that may affect their metabolism due to their close association with obese, type 2 diabetes mellitus. The articles were collected from various online search engines, viz., Google Scholar, PubMed, and Science Direct. Keyword combinations undertaken for the searches were NAFLD, molecular mechanism or epidemiology, dietary factors, or herbal plants. The unmet criteria of the disease should be recognized as earlier as possible to meet the required demands to maintain a healthy lifestyle. However, there are no solid evident studies for the pathogenesis and progression of NAFLD. Insulin resistance and white adipose tissue are playing a vital role in the advancement of steatosis. Herbal plants have been widely utilized to overcome the allopathic side effects and bring a permanent solution for various diseases. The primary purpose of this study is to educate about phytoconstituent’s role, such as flavonoid, saponin, polyphenol, terpenoid, and alkaloid, in ameliorating non-alcoholic steatohepatitis. Herbal plants are utilized as it is well said, “Nature is our best Physician,” it is essential to understand the presence of phytomolecule and their secondary metabolites that may be useful in treating NAFLD-associated disorders.
Keywords: Steatohepatitis, cirrhosis, insulin resistance, white adipose tissue, flavonoids, steatosis, herbals.